Pengaruh wisatawan internasional terhadap pertumbuhan ekonomi Indonesia - Muhammad Arif Kurniawan; Jihad Lukis Panjawa (e-Journal Perdagangan Industri dan Moneter, 2023)
Tourism is a fairly important sector for indonesia, where with indonesia's large tourism potential it is a strong attraction for international tourists to visit indonesia. During the last decades, the relationship between international tourists and economic growth has been the focus of attention of various countries and researchers. The purpose of this study was to determine the effect of macroeconomic variables and international tourists on indonesia's economic growth. In this study, the ecm (error correction model) test method was used and the data used was time series data with a period of 25 years, namely the period 1991-2015. The results of the analysis show that the working workforce, the exchange rate, and the number of international tourist arrivals have an effect on indonesia's economic growth. As for foreign direct investment, the average spending and length of stay of international tourists have no effect on indonesia's economic growth.